Integritas Kepemimpinan Pastoral di Era Postmodern Menurut 2 Timotius 2:14-25 - Hananto, Tri; Yuliantono Adi, Didit (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
The development of technology and information in the global era will have a major influence on human life. Modernist culture has become the choice of the wider community over conventional cultures. Sometimes society loses the social glue that has been the root of culture, which is replaced with the emergence of social media. Apart from that, the development of this technology also has a bad influence on moral ethics, norms and rules in society. However, this development also provides positive insight into the emergence of new leaders, especially leaders in the spiritual world or pastoral leaders who must maintain their integrity. The methodology in this writing uses an exposition approach by paying attention to the verses of God's word contained in 2 Timothy 2:14-25, to get practical application from the figure of a pastoral leader with integrity who keeps his life in accordance with the truth of God's word and by asking for the guidance of the Holy Spirit so that he can protect accountability which has a good influence in the postmodern world.